Strengthening national capacities to implement the International Treaty on Plant Genetic Resources for Food and Agriculture. Report of the mid-term review workshop, 16-19 July 2013 - Vernooy, Ronnie; Halewood, Michael; Otieno, G.; López Noriega, Isabel; Wedajoo, A.; Bioversity International (2013)
The project “Strengthening national capacities to implement the International Treaty on Plant Genetic Resources for Food and Agriculture”, also known as “GRPI 2”, brings together partners from eight countries: Burkina Faso, Côte d’Ivoire, Rwanda, Uganda, Costa Rica, Guatemala, Bhutan and Nepal ; and other organizations. A mid-term review workshop took place, from 16-19 July 2013, at Bioversity International headquarters in Rome. The workshop brought together two external project evaluators, Dr Juliana Santilli from Brazil and Dr Godfrey Mwila from Zambia, and about 30 researchers from the eight project countries and representatives from the University of Illinois at Chicago and Bioversity International. This report summarizes progress made to date and proposes next steps in project implementation.